Islam Pluralis dan Multikulturalisme: Memperkokoh Kesatuan Bangsa - Abdul Rouf (Jurnal Bimas Islam, 2018)
Religious pluralism, internal and external conflicts between religious adherents are real phenomena that remain turbulent in various parts of the world without exception Indonesia. Religious pluralism is one of the post-modernism era fundamental characteristics, specifically confronting a religious person with a dilemmatic situation because he must define himself (who has truth claim) in the midst of other religions and understandings that also have validity. Especially in our country which consists of many religions (Hinduism, Buddhism, Christianity, Catholicism, Confucianism and Islam). Adherents of these religions must live in harmony and peace within the framework of the Indonesia Unitary Republic and each of the people has absolute freedom to choose religion and belief in accordance with their beliefs. However, the conditions of tolerance and peace have not been realized well in our country. In this simple paper, the author tries to provide an Qur'anic perspective on the building national unity concept and religious harmony through a pluralist and inclusive religious understanding as well as giving a place to the multiculturalism principles to support efforts to realize an attitude of openness in order to reach a tolerant - inclusive society. Pluralisme agama, konflik intern dan ekstern antar pemeluk agama adalah fenomena riil yang tetap bergolak di berbagai belahan bumi tanpa kecuali Indonesia. Pluralisme agama merupakan salah satu karakteristik fundamental dari era post-modernisme, secara khusus menghadapkan seorang beragama kepada situasi yang dilematis karena ia harus mendefinisikan dirinya (yang memiliki truth claim) di tengah-tengah agama dan paham lain yang juga mempunyai keabsahan. Khususnya di negara kita yang terdiri banyak agama (Hindu, Budha, Kristen, Katolik, Kong Hucu dan Islam). Pemeluk agama-agama ini, harus hidup rukun dan damai dalam bingkai Negara Kesatuan Republik Indonesia dan masing-masing dari rakyat mempunyai kebebasan mutlak untuk memilih agama dan kepercayaan sesuai dengan keyakinan mereka. Namun demikian, kondisi toleran dan damai belum terwujud secara baik dinegeri kita ini. Dalam tulisan sederhana ini, penulis mencoba memberikan suatu perspektif Alquran tentang konsep membangun kesatuan bangsa dan kerukunan beragama melalui pemahaman agama yang pluralis dan inklusif serta memberi tempat pada prinsip-prinsip multikulturalisme untuk mendukung upaya mewujudkan sikap keterbukaan demi menggapai masyarakat yang toleran – inklusif